ANALISIS KETERLAMBATAN PERAWATAN SHAFT PROPELLER DENGAN METODE FTA DAN FMEA - Adrian Diko Ananto (2022)
In this study, the case of delay in maintenance of the KMP Portlink III Ro-Ro Ship shaft was raised. In this case where shaft maintenance can be done within 2-4 days but in the field it can take up to 10 days. In this case, the cause of the problem and proposed improvements to the problems that occurred at PT. this XYZ. Data processing is carried out with Fault Tree Analysis (FTA) to analyze the process and make system improvements to see possible delays that occur. FTA is an analysis using a graphical model to show a visual analysis of the process, then the cut set method is used to find the combination of events that occur. Labor shortage factor with a failure rate of 0.833. The biggest map timing result is turning which is done for 10 days. Based on FTA, the factors causing delays that have the highest probability of delays are the lack of operators in the workshop and mechanics of PT. XYZ with the probability value of this obstacle is 0.081. Proposed improvements can be made to 5S based on the results of the FMEA (Failure Mode And Effect Analysis) analysis of operator shortages with the resulting RPN number with a value of 900.